PPTI colloquium focused on professional management of the future - UMP, PNC (2019)
Some 100 Universiti Malaysia Pahang (UMP) administrators attended the Administrator Transformation Colloquium titled, ‘Professional Managers of the Future’ that was organised by the Association of Administrative and Professional Officers (PPTI), together with the Registrar Office.